Edukasi pentingnya Partisipasi Pemilih Pemula Dalam pemilihan Umum Mendatang Di SMK Negeri 2 Kota Padangsidimpuan - Harianja, Nurbaya; Patriansyah, Wawan; Eva Juniasih, Tri; Syahputra Marpaung, Indra; Henderlan Harahap, Emirza (COVIT (Community Service of Tambusai), 2023)
In the framework of the success of general elections (elections) in 2023 and the creation of a peaceful democracy, one thing that is being done is through outreach. Currently, the participation of first-time voters in the upcoming election is very important because nearly 20% of the total number of voters are first-time voters. In order for the number of first-time voters to continue to increase, the community service team as academics working at Graha Nusantara University conducted community service in the form of outreach about the importance of first-time voter participation in the upcoming elections. The purpose of this activity is to increase the understanding of novice voters and in this case the students of SMK Negeri 2 Padangsidimpuan who are 17 years and over. This service method is a lecture and a simple simulation about the procedures for choosing a candidate for leadership. This socialization activity was very useful and provided new insights for the participants as seen from the enthusiasm of the participants in asking questions and the results of the questionnaire where more than 80% of the participants answered that they understood the material presented. Keywords: Participation, Beginner Voters, General Elections